2D GaN for Highly Reproducible Surface Enhanced Raman Scattering. Issue 45 (27th September 2021) - Zhao, Shasha; Wang, Huiliu; Niu, Lixin; Xiong, Wenqi; Chen, Yunxu; Zeng, Mengqi; Yuan, Shengjun; Fu, Lei
Abstract: Surface‐enhanced Raman scattering (SERS) based on 2D semiconductors has been rapidly developed due to their chemical stability and molecule‐specific SERS activity. High signal reproducibility is urgently required towards practical SERS applications. 2D gallium nitride (GaN) with highly polar Ga–N bonds enables strong dipole–dipole interactions with the probe molecules, and abundant DOS (density of states) near its Fermi level increases the intermolecular charge transfer probability, making it a suitable SERS substrate. Herein, 2D micrometer‐sized GaN crystals are demonstrated to be sensitive SERS platforms with excellent signal reproducibility and stability. Strong dipole–dipole interaction between the dye molecule and 2D GaN enhances the molecular polarizability. Furthermore, 2D GaN benefits its SERS enhancement by the combination of increased DOS and more efficient charge transfer resonances when compared with its bulk counterpart. Abstract : 2D GaN crystals grown on liquid metals exhibit excellent surface‐enhanced Raman scattering (SERS) performance both in signal sensitivity, reproducibility and stability. Strong dipole–dipole interaction between 2D GaN and probe molecule, abundant density of states near the Fermi level of 2D GaN and increased charge transfer efficiency give rise to enhanced SERS sensitivity with high signal reproducibility.